DESAIN PENELITIAN GROUNDED THEORY: LOGIKA METODOLOGIS DAN KONSTRUKSI TEORI KONTEKSTUAL DALAM PENDIDIKAN - Muhammad Abdillah; Salamah; Dina Hermina (PT. Hasba Edukasi Mandiri, 2026)
Traditional positivist frameworks in educational and social research often over-rely on pre-existing grand theories, resulting in the reduction and